INNOVATIONS OF THE VILLAGE MODEL. (11th November 2018) - Nicholson, R
Abstract: As Villages proliferate, many approaches have been tested to enhance Village sustainability, diversity and better meet the needs of the community being served. One such innovation is the formation of regional coalitions. Interviews with Village coalition leaders (n=18) revealed different approaches to regional coalitions being taken and envisioned. Surveys with 115 operational Villages examined how those part of coalitions differed from non-coalition Villages. Another innovation designed to expand diversity are "no- and low-dues" Villages. Interviews with no- and low-dues Villages (n=21) examined the motivations behind choosing this model as well as the variety of ways such models are sustained without membership dues as a major source of revenue. Interviews also examine these Villages' perspectives on the advantages, disadvantages and challenges of this model. Using survey data (n=115), this presentation will also report quantitative results about how the organizational structure of no- and low- dues Villages differ from other Villages.